Leveraging Sustainable Value Creation Through the Principles of Sustainable Engineering - Cabrita Maria do Rosário; Cruz-Machado Virgílio (E3S Web of Conferences, 2023)
Industrial and technological revolutions have always changed the way companies create value. More recently, sustainability has become a source of inspiration and innovation and most organizations start redesigning their business models based on sustainability concepts. Sustainable practices have become critical issues for industrial engineering, dealing with technological and management principles. Engineering is a major driver of sustainable development by connecting social needs and environmental priorities with appropriate technologies and management practices. According to UNESCO sustainable engineering is about designing and operating daily systems so that the energy and resources they use are sustainable that is, they are used at a rate that safeguards the availability of natural resources for future needs. The literature on the subject is mostly dedicated to technical and design aspects of engineering principles integrating sustainability concepts. Works on how sustainable engineering principles impact sustainable value creation are scarce. Exploring the concepts and the main principles of sustainable value and sustainable engineering, this paper shed light on supporting organizations operationalizing the transition toward business models which are environmentally, socially, and financially sustainable. This work aims to provide a conceptual framework setting out how sustainable engineering principles can provide a thinking guide to connect corporate sustainable value creation drivers and the Sustainable Development Goals (SDGs).